Development of a novel observer-reported outcome measure for the assessment of Respiratory Syncytial Virus (RSV) infection symptoms in pediatric clinical trials - Sandy Lewis; Carla DeMuro; Stan L. Block; Shelly Senders; Paul Wisman; Seth Toback; Jason W. Chien; Valerie Williams (SpringerOpen, 2018)
Abstract Background Respiratory syncytial virus (RSV) is a seasonal infection affecting most children by 2 years of age and the leading cause of lower respiratory tract infection requiring hospitalization in infants. Novel antiviral medications are in development to improve the clinical outcomes of RSV; however, no clinical outcome assessments (COAs) for RSV have been developed in alignment with the United States Food and Drug Administration patient-reported outcome guidance to assist in the evaluation of new therapies. To address this need, an observer-reported outcome (ObsRO) measure designed to assess observable RSV symptoms was created. Methods The literature was reviewed to evaluate existing COAs and identify constructs of interest. Individual caregiver interviews elicited concepts that informed item development, and candidate items were subsequently evaluated in two rounds of cognitive testing. Separate cohorts of caregivers of RSV-infected nonhospitalized and hospitalized infants participated. Therapeutic-area experts provided input throughout the instrument development process. Results Caregivers of 39 children < 24 months old with RSV (31 nonhospitalized, 8 hospitalized) participated in in-depth, individual interviews during concept elicitation and cognitive debriefing, resulting in 21 concepts identified as potentially observable and relevant to young children with RSV. The item pool was reduced to 12 cardinal symptoms and behavior impacts reported to be directly observable by caregivers, with 10 daytime and 9 nighttime symptoms to capture diurnal variation in severity. Conclusions The RSV Caregiver Diary assesses RSV symptom severity and change from the parent or caregiver perspective in a standardized manner to measure treatment benefit. Following psychometric evaluation and refinement, this tool is expected to be suitable for assisting in the clinical development of RSV therapeutics.